Density of Bivalve in the Mangrove Area of Nagari GasanGadang, Padang Pariaman District, West Sumatera - Silvia Ulga; Nur El Fajri; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractMangrove area in the Nagari Gasan Gadang has been damage due to human activities and the damage negatively affects bivalve living in that area. A research aims to understand species and density of bivalve was conducted in July 2019. There were 3 stations with 3 plots/station and 5 sub plots/plot. In each sub plot the bivalve were collected by hand.  There were 2 bivalve species present, they were classified asCorbiculidae family,Polymesodaerosa and Geloina expansa. The density of bivalve ranged from 11,333 to 18,666 organisms/ha and mangrove density ranged from 800 to 1,533 trees/ha. The water qualitywere as follows: temperature 28-30o C, pH 7-8, salinity 17-22 ‰, and dissolved oxygen 1.2-3.6 mg/L, while the soil’s pH was 6-8.In the substrate, organic material ranged from 24.5 to 51.6%  and the type of substrate was sandy mud.Keyword: Corbiculidae,Polymesoda erosa,Geloina expansa, Sandy mud, Water quality